2009
DOI: 10.1021/jf9022146
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Mechanism of Crystalline Cellulose in H3PO4As Assessed by High-Field NMR Spectroscopy and Fast Field Cycling NMR Relaxometry

Abstract: Many processes have been proposed to produce glucose as a substrate for bacterial fermentation to obtain bioethanol. Among others, cellulose degradation appears as the most convenient way to achieve reliable amounts of glucose units. In fact, cellulose is the most widespread biopolymer, and it is considered also as a renewable resource. Due to extended intra- and interchain hydrogen bonds that provide a very efficient packing structure, however, cellulose is also a very stable polymer, the degradation of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Namely, disruption of intra-molecular hydrogen-bonds is crucial to increase the rate of cellulose degradation and enhance yield of glucose achievement (Xiang et al 2003). In previous papers, it has been reported that phosphoric acid is able to withdraw intra-molecular H-bonds in cellulose through formation of phosphor-ester linkages (Zhang et al 2006;Conte et al 2009). Due to this, cellulose dissolves in H 3 PO 4 , thereby consenting achievement of a homogeneous liquid solution (Zhang et al 2006;Conte et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Namely, disruption of intra-molecular hydrogen-bonds is crucial to increase the rate of cellulose degradation and enhance yield of glucose achievement (Xiang et al 2003). In previous papers, it has been reported that phosphoric acid is able to withdraw intra-molecular H-bonds in cellulose through formation of phosphor-ester linkages (Zhang et al 2006;Conte et al 2009). Due to this, cellulose dissolves in H 3 PO 4 , thereby consenting achievement of a homogeneous liquid solution (Zhang et al 2006;Conte et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…)-glucose (CAS N. 492-62-6), and acetonitrile HPLC grade were purchased from Sigma-Aldrich Ò (Milan, Italy) and used without further purification. The characterization of the cellulose is reported elsewhere (Conte et al 2009). …”
Section: Samples and Reactantsmentioning
confidence: 99%
See 3 more Smart Citations